Enhancing neurogenesis and angiogenesis with target delivery of stromal cell derived factor-1α using a dual ionic pH-sensitive copolymer. (August 2015) - Kim, Dong Hee; Seo, Young Kyu; Thambi, Thavasyappan; Moon, Gyeong Joon; Son, Jung Pyo; Li, Guangri; Park, Jae Hyung; Lee, Jung Hee; Kim, Hyeon Ho; Lee, Doo Sung; Bang, Oh Young
Abstract: In this study, we hypothesized that the delivery of molecules that regulate the microenvironment after a cerebral infarction can influence regeneration potential after a stroke. Stromal cell-derived factor-1α (SDF-1α) is a chemoattractant molecule that plays a pivotal role in recruiting endothelial progenitor cells (EPCs) to the infarct region after stroke. Increased SDF-1α expression leads to increased EPCs homing at the infarct region and induces neurogenesis, angiogenesis, neuroprotection, and stem cell homing. Thus, we evaluated the effects of targeted delivery of SDF-1α using a pH-sensitive polymer poly (urethane amino sulfamethazine) (PUASM), a synthetic macromolecule with potential for targeted drug delivery in acidic conditions, to enhance therapeutic neurogenesis and angiogenesis in a rat model of permanent middle cerebral artery occlusion. A dual ionic pH-sensitive copolymer PUASM-based random copolymer was designed and synthesized for the controlled release of SDF-1α in stroke. Owing to the unique characteristics of PUASM, it exhibited a dual ionic pH-sensitive property in an aqueous solution. At pH 8.5, the copolymer exhibited a negative charge and was water soluble. Interestingly, when the pH decreased to 7.4, PUASM could form a micelle and encapsulate protein effectively via the ionic interaction between a negatively charged polymer and a positively charged protein. At pH 5.5, the ionization of tertiary amines led to the disassembly of the micellar structure and released the protein rapidly. Then, we investigated the effect of systemic administration of SDF-1α-loaded pH-sensitive polymeric micelles in a stroke induced rat model. An enzyme-linked immunosorbent assay showed increased expression of SDF-1α in the ischemic region, indicating that the pH-sensitive micelles effectively delivered SDF-1α into the ischemic region. In order to observe the biodistribution of SDF-1α in the ischemic region, it was labeled with the near-infrared dye, Cy5.5. Optical imaging showed that the Cy5.5 signal increased in the infarct region 24 h after administration. Immunohistochemistry data showed that targeted delivery of SDF-1α enhanced neurogenesis and angiogenesis, but did not influence cell survival or inflammation. These observations suggest that SDF-1α-loaded pH-sensitive polymeric micelles can be used as pH-triggered targeting agents and can effectively modify the microenvironment to increase innate neurorestorative processes.